2018
DOI: 10.4103/npmj.npmj_20_18
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Vitamin A deficiency among under-five children in South-Western Nigeria

Abstract: The prevalence of VAD among Nigerian children appears to have reduced, compared with previous reports; however, further studies are required to assess the current national prevalence, so as to design programmes that can achieve further reduction in the proportion of children affected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Vitamin A deficiency in young children is a significant public health concern in Nigeria; a 2006 nationally representative survey of children under 5 years of age in Nigeria reported that rates of VAD ranges from 25–31% [ 28 ]. However, a recent 2018 report of 170 Southwestern Nigerian children under 5 years of age indicated that the rate of VAD was 5.3%, suggesting that there may be regional differences in rates of VAD, or the effectiveness of public health interventions in this area [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin A deficiency in young children is a significant public health concern in Nigeria; a 2006 nationally representative survey of children under 5 years of age in Nigeria reported that rates of VAD ranges from 25–31% [ 28 ]. However, a recent 2018 report of 170 Southwestern Nigerian children under 5 years of age indicated that the rate of VAD was 5.3%, suggesting that there may be regional differences in rates of VAD, or the effectiveness of public health interventions in this area [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to this high burden of vitamin A deficiency and its clinical consequences, the WHO recommends vitamin A supplementation for infants and children between 6 and 59 months in areas where vitamin A deficiency is a public health problem 5. This intervention has been shown to reduce the risk of all-cause mortality by 24%1 and reduced the prevalence of vitamin A deficiency over time as reported in some areas in Nigeria 6,7…”
Section: Discussionmentioning
confidence: 94%
“…This finding is consistent with studies done in Sudan, the Tigray region, and India [18]. This might be due to the reason that the big family size had reduced the children's share of energy-, protein-, iron-, and vitamin A-rich sources of foods and led to an increase in the chance of illness resulting in the reduced appetite of children for foods containing vitamin A, and in turn, causing night blindness as a manifestation of vitamin A deficiency [20]. In this study, the children from illiterate mothers were 3 times more likely to have night blindness as compared to the preschool children from literate mothers.…”
Section: Discussionmentioning
confidence: 99%